Correlation between neutrophil to lymphocyte ratio and platelet to lymphocyte ratio with proteinuria in different stages of chronic kidney disease - Fathima Azra Aneez; Nifla Shariffdeen; Fathima Asra Haleem; Brammah R Thangarajah; Karunaithas Rasaratnam (SpringerOpen, 2024)
Abstract Background Chronic kidney disease (CKD) is a progressive failure of renal function with ongoing systemic inflammation. Inflammatory markers such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and proteinuria were documented as independent predictors of CKD progression. Although proteinuria estimated by the protein to creatinine ratio (UPCR) is generally employed to screen the disease progression of CKD, the correlation of NLR and PLR with different stages of CKD is yet to be studied. Consequently, this study strived to find the stage-wise correlation between NLR and PLR with proteinuria in CKD patients. Methods Eighty-five CKD patients with proteinuria who visited the Nephrology Clinic at Teaching Hospital Jaffna, Sri Lanka, were randomly selected and categorized as stages II to IV based on the estimated glomerular filtration rate (e-GFR). Blood samples were collected and subjected to investigate patients' NLR and PLR. Furthermore, urine protein and creatinine were measured and UPCR was calculated. Participants' demographic, clinical, and laboratory data were obtained from patients' clinical registry. Spearman's rank correlation and receiver operative characteristic (ROC) curve analysis was done, and the p value < 0.05 was considered statistically significant. Results Amongst the total participants, males were predominant (58.8%), with a mean age of 58.1. Severity analysis based on the e-GFR revealed that 17.64%, 18.82%, 29.41%, and 34.11% of CKD patients were in stages II, IIIA, IIIB, and IV, respectively. Stage-wise correlation and ROC curve analysis indicated that NLR and PLR were positively correlated with UPCR in stages IIIA, IIIB, and IV of CKD with more than 80% predictive sensitivity and specificity. Conclusion NLR and PLR can be used as novel predictive markers for monitoring the severity of CKD; however, further large-scale cohort studies of NLR and PLR with serial monitoring and multiple closely spaced measurements are recommended to develop these markers into clinically acceptable markers for CKD progression.